Preparation method of porous starch with stable structure
Porous starch is prepared by two-step methods of "melting coating" and "directional hydrolysis", which solves the problem of instability in the structure of porous starch and difficult to balance the porous formation effect in the prior art, and achieves the preparation of porous starch with high adsorption, structural stability and thermal stability.
Patent Information
- Application Number
- CN202510063044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In the existing porous starch preparation methods, the enzymatic method has the problem of instability in the particle structure, the chemical treatment has the problem of introducing chemical groups, and the common problem of difficulty in balancing the pore-structure stability of the physical method and the enzymatic method.
Structurally stable porous starch was prepared by two-step method of "melting coating" and "directional hydrolysis". The starch particles are swelled by the melt coating method and formed an unstructured mesh structure. In combination with the directional hydrolysis method, enzymes are used to perform directional hydrolysis on the surface of the particles to ensure the stability of the particle structure.
The prepared porous starch has excellent adsorption, structural stability and thermal stability, with obvious adsorption rate and complete particle structure. It is suitable for starch raw materials of different crystal forms and particle sizes. It has a simple process and low cost.
Smart Images

Figure CN119798769A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified starch processing, and particularly relates to a method for preparing structurally stable porous starch. Background Art
[0002] Porous starch is a modified starch with a honeycomb pore structure and a high specific surface area. Compared with natural starch, porous starch has better adsorption properties, which makes it widely used in many fields such as food, pharmaceuticals, chemicals, cosmetics and agriculture. At present, the preparation methods of porous starch mainly include physical, chemical, enzymatic and composite modification.
[0003] In existing academic papers, there are many studies on the use of enzymatic methods to prepare porous starch, such as: Zhang Huanhuan et al. (Zhang Huanhuan, Zhi Qi. Research on the process of preparing chestnut microporous starch by dual enzyme method [J]. Food Industry, 2017, 38 (02): 81-84.) used the dual enzyme method to prepare chestnut microporous starch, which has a good adsorption effect, but takes a long time (20h); Benavent-Gil et al. (Benavent-Gil Y, Rosell M C. Comparison of porous starches obtained from different enzyme types and levels [J]. Carbohydrate Polymers, 2017, 157533-540.) found that different enzymes have different effects on the formation of starch porous structure. The thermal properties results of this study show that the starch treated with enzymes has a lower melting onset temperature and melting peak temperature (usually the melting temperature is low and the thermal stability of the particles is poor). Porous starch prepared by physical method usually has good structural stability. For example, Yu Liyue (Yu Liyue. Research on the preparation and adsorption application of potato porous starch [D]. Gansu Agricultural University, 2020.) stated that the porous starch prepared by physical method has stable structure, but the pore-forming effect is limited. In order to improve the pore-forming effect of porous starch, researchers also combined physical method with enzymatic method to prepare porous starch, but there is still the problem of difficulty in balancing stability and pore-forming effect, such as Zahra et al. (Zahra D, Hossein MA, Mohsen B. Porous corn starch obtained from combined cold plasma and enzymatic hydrolysis: Microstructure and physicochemical properties [J]. International journal of biological macromolecules, 2022, 223 (PA): 790-797.) Corn porous starch was prepared by combining cold plasma treatment and enzymatic hydrolysis. The adsorption effect of the starch was significantly improved. However, compared with single enzymatic hydrolysis, the particle crystallinity decreased and the gelatinization enthalpy decreased, indicating that the stability of its particle structure decreased; Zhang Tiantian et al. (Zhang Tiantian, Hou Mengxing, Liu Peiling. Preparation of cross-linked porous starch by high static pressure synergistic enzyme method and study on its properties [J]. Journal of Chinese Institute of Food Science and Technology, 2022, 22 (12): 153-164.) High static pressure and α-amylase and saccharifying enzyme were used to prepare high-pressure porous starch, and then sodium trimetaphosphate was used to cross-link and modify the starch. The prepared porous starch had excellent pore formation. However, the Fourier infrared results showed that the short-range ordered structure was destroyed and the crystallinity was reduced, indicating that the prepared porous starch particles had poor stability and the preparation method was complicated.
[0004] The Chinese invention patent with application number 202311273085.6 discloses a porous starch with free radical scavenging function and its preparation method and application. The patent uses an enzymatic method to prepare a porous starch with free radical scavenging function and explores its adsorption. The study found that the prepared porous starch has a good pore-forming effect, but the thermogravimetric results show that the initial thermal decomposition temperature of the prepared porous starch is low, and the porous starch has poor heat resistance; the Chinese invention patent with application number 202310131810.X discloses a modified starch and its preparation method. A kind of adsorption of harmful gases in flue gas is prepared by combining an enzymatic method with a cross-linking method. Although the porous starch with good adsorption effect has good adsorption and stability, the chemical group amino group needs to be introduced through the cross-linking agent epichlorohydrin (toxic and corrosive) during the cross-linking process, and the preparation method is complicated; Chinese invention patent application number 202210118863.3 discloses cross-linked corn porous starch loaded with curcumin composite gel microspheres and a preparation method thereof. Corn porous starch is prepared by pulsed electric field assisted enzymatic hydrolysis, and further processed by cross-linking method, and composite gel microspheres are prepared with carboxymethyl cellulose and other substances as auxiliary materials to load and embed curcumin. The prepared sample has good embedding effect, but the preparation method is complicated and the cost is high.
[0005] In summary, in the prior art, the enzymatic preparation of porous starch has the problem of unstable particle structure, and the chemical treatment has the problem of introducing chemical groups. Although physical treatment has the advantage of cleaning, the common physical methods such as ultrasound and cold plasma combined with enzymatic treatment still cannot well balance the inherent common problem of pore formation-structural stability. Preparing gel microspheres after embedding active substances in porous starch is a common method to improve the retention rate of active substances in porous starch and the stability of particles, but it still has limitations such as complex operation and long preparation cycle. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies of the above-mentioned prior art and provide a method for preparing a structurally stable porous starch. The method has a simple process and low manufacturing cost. The prepared porous starch has excellent adsorption, structural stability and thermal stability.
[0007] To achieve the purpose of the present invention, the present invention adopts the following technical solutions:
[0008] A method for preparing a structurally stable porous starch comprises the following steps:
[0009] (1) Melt coating: Add a hydrophilic colloid into deionized water to prepare a solution, then add starch, mix well, and obtain a composite suspension, heat it to the temperature at which the crystal begins to melt, and then vacuum freeze-dry and sieve to obtain melt-coated starch;
[0010] (2) Directed hydrolysis: Add the molten coated starch to a citric acid-disodium hydrogen phosphate buffer solution and mix well to obtain a starch-buffer solution suspension. Add enzyme to carry out an oscillating hydrolysis reaction. After the reaction is completed, adjust the reaction solution to alkaline to terminate the reaction, then adjust to neutral, and finally centrifuge, wash, vacuum freeze-dry, grind and sieve to obtain a structurally stable porous starch.
[0011] Furthermore, in step (1), the hydrophilic colloid is one or a mixture of any proportion of two or more of plant-derived hydrophilic colloids (pectin, locust bean gum, carrageenan, gum arabic), animal-derived hydrophilic colloids (gelatin, chitosan), microbial-derived hydrophilic colloids (such as dextran, xanthan gum), and non-starch polysaccharides (such as cellulose, hemicellulose).
[0012] Furthermore, in step (1), the starch is one or a mixture of any proportion of two or more of cereal starch (ordinary corn starch, waxy corn starch, rice starch, millet starch, wheat starch), potato starch (potato starch, tapioca starch, sweet potato starch), bean starch (mung bean starch, pea starch), or other vegetable sources (water chestnut starch, lotus root starch).
[0013] Furthermore, in step (1), the amount of the hydrophilic colloid added is 0.1% to 10% of the dry weight of the starch.
[0014] Furthermore, in step (1), the temperature of the heating treatment is a temperature at which the starch crystals are completely melted as measured by a differential scanner and fluctuates within ±5°C, and the time of the heating treatment is 15 min to 100 min.
[0015] Furthermore, in step (2), the amount of the melt-coated starch added to every 100 mL of citric acid-disodium hydrogen phosphate buffer solution is (25-45) g, and the pH value of the citric acid-disodium hydrogen phosphate buffer solution is 5.6-6.4.
[0016] Furthermore, in step (2), the enzyme is one or a mixture of any proportion of α-amylase, β-amylase, γ-amylase, isoamylase or saccharifying enzyme, and the amount of the enzyme added is 40U / g to 180U / g of the dry basis mass of starch.
[0017] Furthermore, in step (2), the conditions of the oscillation hydrolysis reaction are 120-200 r / min, 25° C.-60° C., and 4 h-12 h.
[0018] Furthermore, in step (2), the centrifugal speed is 3000-4000 r / min, the time is 5 min-25 min, and the screening is through a 200-mesh sieve.
[0019] The porous starch is prepared by the above preparation method.
[0020] Beneficial effects of the present invention:
[0021] 1) The present invention provides a method for preparing a structurally stable porous starch, which innovatively uses a two-step method of "melt coating" and "directional hydrolysis" to prepare a structurally stable porous starch. After melt treatment, the starch granules swell, exposing structurally fragile sites in the granules, and the hydrophilic colloids extend and coat the surface of the starch granules and associate with the soluble starch leached during the melting process to form an unstructured network structure on the surface of the granules, which is melt coating of the granules to ensure the steady-state hydrolysis of the starch granules. At the same time, the micro-concave sites formed by the accumulation of hydrophilic colloids on the surface of starch granules are used to provide reaction sites for enzymatic hydrolysis to achieve directional hydrolysis of the enzyme.
[0022] 2) The method of the present invention has a simple preparation process and low manufacturing cost. The prepared porous starch has a distinct pore structure. The scanning electron microscope results and ordinary microscope both show that the granule structure is complete. Compared with native starch, the porous starch prepared by the present invention has an adsorption rate of 103.24%, 138.33%, 55.90% and 73.70% for water, oil, vitamin C and methylene blue, respectively, and has better structural stability and thermal stability (crystallization increased by 3.75%, and melting onset temperature increased by 7°C), providing an effective way for the embedding, adsorption and sustained release of bioactive ingredients.
[0023] 3) The method of the present invention is applicable to starch raw materials with different crystal forms and different particle sizes. The preparation method is simple and the production efficiency is high. The method used has the advantages of being green and clean (safe), having a high raw material utilization rate (cost), and having a good steady-state loading effect (application value), which is conducive to later applications and promotes industrial development. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Optical microscope images and polarizing microscope images of porous starch prepared in Example 1 and Comparative Examples 1-2;
[0025] Figure 2 The scanning electron microscope images and laser confocal images of the porous starch prepared in Example 1 and Comparative Examples 1-2;
[0026] Figure 3 This is a scanning electron microscope image of the porous starch prepared in Example 2-4;
[0027] Figure 4 The transparency test results of the porous starch prepared in Example 1 and Comparative Examples 1-2;
[0028] Figure 5 The hydrolysis rate and yield test results of the porous starch prepared in Example 1 and Comparative Example 2;
[0029] Figure 6 Thermal properties of porous starch prepared in Example 1 and Comparative Examples 1-2;
[0030] Figure 7 The infrared spectra and corresponding deconvolution spectra of the porous starch prepared in Example 1 and Comparative Examples 1-2;
[0031] Figure 8 These are the test results of vitamin C adsorption rate, methylene blue adsorption rate, water absorption rate and oil absorption rate of the porous starch prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions of this application will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] Example 1
[0034] A method for preparing a structurally stable porous starch comprises the following steps:
[0035] (1) Melt coating: 0.12 g of xanthan gum was added to 120 mL of deionized water to prepare a solution, and then 40 g (dry basis) of common corn starch was added and mixed uniformly to obtain a composite suspension. Then, the composite suspension was heated for 30 min at a temperature at which starch crystals began to melt (the melting start temperature of starch was measured in advance using a differential scanner, and this was used as the crystal melting start temperature), and finally vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain melt-coated starch;
[0036] (2) Directed hydrolysis: The molten coated starch was added to a citric acid-disodium hydrogen phosphate buffer solution (pH = 5.6) (3 mL of citric acid-disodium hydrogen phosphate buffer solution was used for every 1 g of molten coated starch), mixed evenly, and a starch-buffer solution suspension was obtained. After keeping the mixture at 55°C for 10 min, α-amylase (80 U / g of enzyme added based on the dry basis of starch) was added, and the mixture was subjected to hydrolysis reaction at 55°C with shaking (190 r / min) for 9 h. After the reaction, the reaction mixture was adjusted to alkaline (pH 10.8) with 1 mol / L sodium hydroxide solution to terminate the reaction. After 15 min, the mixture was adjusted to neutral with 1 mol / L hydrochloric acid solution. Finally, the mixture was centrifuged (at a speed of 3500 r / min for 10 min), washed, vacuum freeze-dried (-80°C, 72 h), ground, and passed through a 200-mesh sieve to obtain a structurally stable porous starch.
[0037] Comparative Example 1
[0038] Preparation of melt-coated starch: 0.12 g of xanthan gum was evenly dispersed in 120 mL of deionized water to prepare a solution, 40 g of dry basis ordinary corn starch was added, and the mixture was evenly mixed to obtain a composite suspension. Then, the composite suspension was heated for 30 min at a temperature at which the starch crystals began to melt (the melting start temperature of the starch was measured in advance using a differential scanner, and this was used as the crystal melting start temperature), and finally vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain melt-coated starch.
[0039] Comparative Example 2
[0040] Preparation of enzymatic porous starch: ordinary corn starch and citric acid-disodium hydrogen phosphate buffer solution (pH = 5.6) are mixed in a ratio of 1:3 (3 mL of citric acid-disodium hydrogen phosphate buffer solution is used for every 1 g of ordinary corn starch) to obtain a starch suspension, which is kept warm at 55°C for 10 min, and then α-amylase (based on starch dry basis, the enzyme addition amount is 120 U / g) is added to the starch suspension, and the hydrolysis reaction is carried out at 55°C constant temperature oscillation (190 r / min) for 15 h. After the reaction, 1 mol / L sodium hydroxide solution is used to adjust the solution to alkalinity (pH value is 10.8) to terminate the reaction. After 15 min, hydrochloric acid solution is used to adjust the solution pH to neutral, and finally centrifuged (at a speed of 3500 r / min for 10 min), washed, vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain enzymatic porous starch.
[0041] Example 2
[0042] A method for preparing a structurally stable porous starch comprises the following steps:
[0043] (1) Melt coating: 0.04 g of xanthan gum was added to 120 mL of deionized water to prepare a solution, and then 40 g (dry basis) of common corn starch was added and mixed uniformly to obtain a composite suspension. Then, the composite suspension was heated for 30 min at a temperature at which starch crystals began to melt (the melting start temperature of starch was measured in advance using a differential scanner, and this temperature was used as the crystal melting start temperature), and finally vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain melt-coated starch;
[0044] (2) Directed hydrolysis: The molten coated starch was added to a citric acid-disodium hydrogen phosphate buffer solution (pH = 6.4) (3 mL of citric acid-disodium hydrogen phosphate buffer solution was used for every 1 g of molten coated starch), mixed evenly, and a starch-buffer solution suspension was obtained. After keeping the mixture at 55°C for 10 min, α-amylase (80 U / g of enzyme added based on the dry basis of starch) was added, and the mixture was subjected to hydrolysis reaction at 55°C with shaking (190 r / min) for 12 h. After the reaction, the reaction mixture was adjusted to alkaline (pH 10.8) with 1 mol / L sodium hydroxide solution to terminate the reaction. After 15 min, the mixture was adjusted to neutral with 1 mol / L hydrochloric acid solution. Finally, the mixture was centrifuged (at a speed of 3500 r / min for 10 min), washed, vacuum freeze-dried (-80°C, 72 h), ground, and passed through a 200-mesh sieve to obtain a structurally stable porous starch.
[0045] Example 3
[0046] A method for preparing a structurally stable porous starch comprises the following steps:
[0047] (1) Melt coating: 0.40 g of xanthan gum was added to 120 mL of deionized water to prepare a solution, and then 40 g (dry basis) of common corn starch was added and mixed uniformly to obtain a composite suspension. Then, the composite suspension was heated for 30 min at a temperature at which starch crystals began to melt (the melting start temperature of starch was measured in advance using a differential scanner, and this was used as the crystal melting start temperature), and finally vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain melt-coated starch;
[0048] (2) Directed hydrolysis: The molten coated starch was added to a citric acid-disodium hydrogen phosphate buffer solution (pH = 5.6) (3 mL of citric acid-disodium hydrogen phosphate buffer solution was used for every 1 g of molten coated starch), mixed evenly, and a starch-buffer solution suspension was obtained. After keeping the mixture at 55°C for 10 min, α-amylase (the amount of enzyme added was 60 U / g based on the dry basis of starch) was added, and the hydrolysis reaction was carried out at 55°C with shaking (190 r / min) for 12 h. After the reaction, the reaction solution was adjusted to alkaline (pH value was 10.8) with 1 mol / L sodium hydroxide solution to terminate the reaction. After 15 min, the reaction solution was adjusted to neutral with 1 mol / L hydrochloric acid solution. Finally, the mixture was centrifuged (at a speed of 3500 r / min for 10 min), washed, vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain a structurally stable porous starch.
[0049] Example 4
[0050] A method for preparing a structurally stable porous starch comprises the following steps:
[0051] (1) Melt coating: 0.20 g of xanthan gum was added to 120 mL of deionized water to prepare a solution, and then 40 g (dry basis) of common corn starch was added and mixed uniformly to obtain a composite suspension. Then, the composite suspension was heated for 30 min at a temperature at which starch crystals began to melt (the melting start temperature of starch was measured in advance using a differential scanner, and this was used as the crystal melting start temperature), and finally vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain melt-coated starch;
[0052] (2) Directed hydrolysis: The molten coated starch was added to a citric acid-disodium hydrogen phosphate buffer solution (pH = 6) (3 mL of citric acid-disodium hydrogen phosphate buffer solution was used for every 1 g of molten coated starch), mixed evenly, and a starch-buffer solution suspension was obtained. After keeping the mixture at 55°C for 10 min, α-amylase (the amount of enzyme added was 100 U / g based on the dry basis of starch) was added, and the hydrolysis reaction was carried out at 55°C with shaking (190 r / min) for 6 h. After the reaction, the reaction solution was adjusted to alkaline (pH value was 10.8) with 1 mol / L sodium hydroxide solution to terminate the reaction. After 15 min, the reaction solution was adjusted to neutral with 1 mol / L hydrochloric acid solution. Finally, the mixture was centrifuged (at a speed of 3500 r / min for 10 min), washed, vacuum freeze-dried (-80°C, 72 h), ground and passed through a 200-mesh sieve to obtain a structurally stable porous starch.
[0053] Figure 1 The optical microscope and polarizing microscope images of the porous starch prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 1It can be seen that the starch samples of ordinary corn starch and comparative example 1 have larger starch granules and a complete polarized cross structure, indicating that the starch treated by melt coating retains its original morphology and structural characteristics. In contrast, radial shadows were observed in the starch prepared in comparative example 2 and Example 1, and we speculate that it is the pore structure of the starch granules. Among them, the structure of comparative example 2 is fragile. Under the observation of an optical microscope, many broken starch granules can be clearly seen, and the polarized intensity is weakened, indicating that although comparative example 2 (enzymatic treatment only) can form larger holes, its structure is unstable. However, the porous starch prepared in Example 1 can not only clearly observe the obvious hole channels inside the particles, but also most of the starch in Example 1 still has a structurally complete polarized cross structure, with few damaged particles, indicating that the porous starch prepared in Example 1 has good structural stability.
[0054] Figure 2 The scanning electron microscope and laser confocal images of the porous starch prepared in Example 1 and Comparative Examples 1-2 show that the edges of ordinary corn starch particles are clear, the surface is smooth, there are a small number of micropores, and the internal structure is complete without obvious channels or cracks. It can be seen from the laser confocal results that compared with ordinary corn starch, the edges of the particles of Comparative Example 1 after "melt coating" treatment are blurred. It can be seen from the electron microscope image that a mixture of soluble starch and hydrophilic colloid is accumulated on the surface of Comparative Example 1. This shows that the melt coating method used in the present invention can effectively "coat" the particles with non-grid interface distribution, thereby providing sites for "directional hydrolysis". Comparative Example 2 (enzyme hydrolysis only) and Example 1 after enzymatic hydrolysis both have obvious pore structures. Among them, the porous starch prepared in Comparative Example 2 has a significant pore-forming effect, but its structure is severely damaged, the interior collapses, and the original structural stability is lost. In contrast, Example 1 not only has a better pore-forming effect, but also the particles are more complete, showing significant structural stability. This is consistent with the results of optical microscopy and polarizing microscopy. In addition, the mesh film layers formed by the melt coating can be clearly observed on the surface of Example 1. These film layers can not only play a role in stabilizing the particle structure, but also the depressions formed by the mesh film layers can allow the particle surface to adsorb active substances, thereby improving the embedding rate.
[0055] Figure 3 This is a scanning electron microscope image of the porous starch prepared in Example 2-4. It can be seen from the image that the porous starch prepared in Example 2-4 all have good pore-forming effect and structural stability, indicating that the method of preparing structurally stable porous starch by the two-step method of "melt coating" and "directional hydrolysis" is feasible.
[0056] The transparency, hydrolysis rate and yield, water absorption / oil absorption rate, vitamin adsorption rate and methylene blue adsorption rate of the porous starch prepared in Example 1 and Comparative Examples 1-2 were tested. The relevant testing methods are as follows:
[0057] 1. Transparency determination method: Accurately weigh 0.40g (dry basis) of common corn starch, the porous starch prepared in Comparative Examples 1-2 and Example 1, and mix them evenly with 40mL of deionized water to prepare a starch suspension, which is then heated in a water bath with boiling water and stirred evenly for 20min. After cooling for a period of time, take an appropriate amount of starch paste and pour it into a cuvette, and measure the transmittance of the starch paste at 620nm with an ultraviolet spectrophotometer, and measure the transmittance of the starch paste after 0h, 24h, 48h and 72h, i.e., transparency.
[0058] 2. Determination of hydrolysis rate and yield: The DNS method was used to determine the hydrolysis rate. (1) Preparation of glucose standard curve: Take 1g of glucose and place it in an oven at 80℃ to dry until constant weight. After taking it out, accurately weigh 0.0500g of glucose and dissolve it in distilled water. The volume was adjusted to 50mL to prepare a 1mg / mL glucose standard solution, which was diluted with distilled water to 0.1mg / mL, 0.2mg / mL, 0.3mg / mL, 0.4mg / mL, and 0.5mg / mL glucose solutions. Take 0.5mL of glucose solutions of different concentrations and place them in a light-proof test tube containing 1.5mL of DNS solution. After reacting in a boiling water bath for 5min, quickly cool to room temperature, add 4mL of distilled water to each tube, and let it stand for 20min. Use a spectrophotometer to measure the corresponding absorbance at a wavelength of 540nm to obtain a standard curve. The relationship between glucose concentration (y) and absorbance (x) is y=2.2905x+0.0213(R 2 =0.998). (2) Determination of sample hydrolysis rate: Weigh a certain mass of starch for enzymatic hydrolysis. After the reaction is terminated, centrifuge the starch milk. Take 0.5 mL of the supernatant diluted a certain number of times and measure its absorbance according to the method of (1). The starch hydrolysis rate can be calculated by the following formula. (3) Determination of yield: Centrifuge the starch milk after enzymatic hydrolysis, wash and dry the precipitate, and weigh it. The yield can be calculated by the following formula.
[0059]
[0060] Where, C is the concentration obtained by regression line equation of absorbance measured by DNS method after dilution, g / mL; N is the dilution multiple; V is the volume of supernatant, mL; M 1 is the mass of starch, g; M 2 is the mass of porous starch obtained after treatment, g.
[0061] 3. Test method for water / oil absorption rate: Accurately weigh 0.40g (dry basis) of starch in a centrifuge tube, add 5mL of distilled water (soybean oil) to the tube and stir to mix, absorb for 30min at room temperature, centrifuge for 10min to remove the distilled water (soybean oil) on the upper layer, and accurately weigh the total mass of the remaining sediment and the centrifuge tube. The water absorption rate (oil absorption rate) of starch can be calculated by the following formula:
[0062]
[0063] In the formula, weigh the mass of the centrifuge tube and powder, recorded as M 1 , g; the mass of the precipitate and the centrifuge tube after adsorption is recorded as M 2 , g.
[0064] 4. Determination of vitamin adsorption rate: (1) Determination of standard curve: Prepare vitamin C solutions with a gradient of 5 mg / L and a concentration of 5 to 40 mg / L, and measure the absorbance A at 265 nm using an ultraviolet spectrophotometer to obtain a standard curve. The relationship between vitamin C concentration (y) and absorbance (x) is y = 29.555-1.274 (R 2 =0.9978). (2) Adsorption of vitamin C: Accurately weigh 1g (dry basis) sample, then add 25mL of 20mg / mL vitamin C solution, and adsorb on a constant temperature shaker (150r / min, 25°C) for a period of time, then centrifuge (3000r / min, 25°C, 5min) to obtain the supernatant. Measure the absorbance of the supernatant and convert it into concentration against the standard curve. The adsorption rate of porous starch to vitamin C solution can be calculated by the following formula:
[0065]
[0066] Wherein, V: volume of vitamin C solution, mL; Co: initial concentration of solution, mg / L; Ce: equilibrium concentration of solution, mg / mL.
[0067] 5. Determination of methylene blue adsorption rate: (1) Determination of standard curve: Prepare methylene blue solutions with a gradient of 1 mg / L and a concentration of 1 to 10 mg / L, and measure the absorbance at 665 nm using an ultraviolet spectrophotometer to obtain a standard curve. The relationship between the methylene blue concentration (y) and the absorbance (x) is y = 5.9387x - 0.235 (R 2=0.9981). (2) Adsorption of methylene blue: Accurately weigh 100 mg (dry basis) of sample, then add 40 mL of 50 mg / mL methylene blue solution, and adsorb on a constant temperature shaker (150 r / min, 25°C) for a period of time, centrifuge (3000 r / min, 25°C) for 5 min to obtain the supernatant. Measure the absorbance of the supernatant and convert it into concentration by checking the standard curve. The adsorption rate of porous starch to methylene blue solution can be calculated by the following formula:
[0068]
[0069] Wherein, V: volume of methylene blue solution added, mL; Co: initial concentration of solution, mg / L; Ce: equilibrium concentration of solution, mg / mL.
[0070] Figure 4 The transparency test results of the porous starch prepared in Example 1 and Comparative Examples 1-2 are shown in the figure. As can be seen from the figure, compared with the unhydrolyzed ordinary corn starch and the starch prepared in Comparative Example 1, the transparency of the starch granules in Comparative Example 2 and Example 1 is significantly increased. This may be because α-amylase acts on α-1,4 glycosidic bonds. After enzymatic hydrolysis, the starch glycosidic bonds are broken and the chain length becomes shorter, which is conducive to the better dissolution of starch granules in water, so the transparency is increased. The transparency of the starch prepared in Comparative Example 1 is lower than that of the untreated ordinary corn starch, which shows that the sample after melt coating treatment is not easy to be gelatinized, which is conducive to improving stability. Compared with Comparative Example 2, the transparency of the porous starch prepared in Example 1 is significantly reduced, and the trend does not change with the change of time (0h~72h), indicating that the two-step method of "melt coating" and "directional hydrolysis" can significantly improve the thermal stability of the particles and the prepared starch has good storage performance.
[0071] Figure 5 The hydrolysis rate and yield test results of the porous starch prepared in Example 1 and Comparative Example 2. Generally, the yield is negatively correlated with the degree of hydrolysis, and the hydrolysis rate is positively correlated with the degree of hydrolysis, and this trend is also shown in the figure. The degree of hydrolysis of Comparative Example 2 is higher, but combined with the analysis of the electron microscopy results, the particle structure of Comparative Example 2 collapsed, forming a huge cavity, and the particle structure stability was poor, indicating that a single enzymatic hydrolysis caused excessive hydrolysis of the particles, resulting in poor particle structure stability. In contrast, the porous starch prepared by the two-step method of "melt coating" and "directional hydrolysis" can form a significant pore structure and has good structural stability. In addition, the high yield makes the porous starch prepared in Example 1 also have certain advantages in terms of economic benefits.
[0072] Figure 6The thermal properties of porous starch prepared in Example 1 and Comparative Examples 1-2 are shown in the figure. As shown in the figure, compared with common corn starch without enzymatic hydrolysis treatment and Comparative Example 1, the melting starting temperature of porous starch prepared in Comparative Example 2 and Example 1 is significantly increased, and the melting starting temperature of Example 1 is higher than that of Comparative Example 2. Usually, the initial melting temperature is positively correlated with thermal stability. The melting starting temperature of Example 1 is 73.84°C, which is significantly higher than that of common corn starch (66.16°C) and Comparative Example 2 (70.21°C), which shows that the two-step method of "melt coating" and "directional hydrolysis" can significantly improve the thermal stability of starch granules.
[0073] Figure 7 The infrared spectra and corresponding deconvolution spectra of the porous starch prepared in Example 1 and Comparative Examples 1-2 are shown, wherein: Figure 7 A is the infrared spectrum, Figure 7 B is the corresponding deconvolution spectrum. As can be seen from the figure, the characteristic absorption peak position of starch did not change before and after each treatment, indicating that the treatment did not cause changes in starch-related groups. -1 and 1022cm -1 The absorption peaks at 1047 and 1022 cm are related to the crystalline structure and amorphous structure, respectively. Therefore, the ratio of the two is often used. -1 ) characterizes the short-range order of starch structure, and the larger the R value, the higher the order of structure. Compared with ordinary corn starch, the short-range order of Comparative Example 2 is reduced, and the particle damage caused by excessive random hydrolysis may be the main reason for the reduction of its order. At the same time, the short-range order of Example 1 is significantly higher than that of Comparative Example 2, from 0.74 cm -1 (Comparative Example 2) increased to 0.93 cm -1 (Example 1). This is mainly because "melt coating" provides a rough surface for the particles, which is conducive to the attachment of enzymes. In addition, the non-structural coating on the particle surface allows the enzyme to attack the area exposed by the surface coating in a directional manner, providing a hydrolysis site for the subsequent "directional hydrolysis". Therefore, "melt coating" can effectively promote the enzyme molecules to directional hydrolyze the amorphous areas of starch particles, thereby increasing the degree of crystallization of the porous starch particles prepared by the two-step method of "melt coating" and "directional hydrolysis" and improving the structural stability.
[0074] Table 1
[0075]
[0076] Table 1 shows the long-range crystal structure parameters of starch granules prepared in Example 1 and Comparative Examples 1-2. Relative crystallinity RC% is the proportion of the crystalline area in the total area (the sum of the crystalline area and the non-crystalline area) in the diffraction pattern, which is usually used to characterize the long-range crystal structure of the granules. Enzymatic hydrolysis usually preferentially hydrolyzes the amorphous region, so the starch granules after enzymatic hydrolysis have a higher degree of crystallinity.
[0077] As can be seen from Table 1, the characteristic peaks of Comparative Examples 1 to 2 and Example 1 have not changed, so the crystal type of the particles has not changed and is still a type A crystal structure. The relative crystallinity of Example 1 increased from 20.35% (ordinary corn starch) to 24.10%, indicating that the two-step method of "melt coating" and "directional hydrolysis" can significantly improve the stability of the particles. The relative crystallinity of Comparative Example 2 is lower than that of ordinary corn starch. This may be because the structure of the particles is destroyed due to random over-hydrolysis, resulting in a decrease in relative crystallinity. The relative crystallinity of Example 1 is much higher than that of the comparative example and ordinary corn starch, indicating that the two-step method of "melt coating" and "directional hydrolysis" has a good promoting effect on the stability of the particle structure.
[0078] Figure 8 The test results of the vitamin C adsorption rate, methylene blue adsorption rate, water absorption rate and oil absorption rate of the porous starch prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 8 A is the test results of vitamin C adsorption rate and methylene blue adsorption rate. Figure 8 B is the test results of water absorption and oil absorption. It can be seen from the figure that compared with the original starch with smooth surface, the starch particles after "melt coating" have more significant adsorption effect. This may be due to the presence of a pile layer of hydrophilic colloid mixed with soluble starch on the surface of the "melt coating" particles. The pile layer not only increases the adsorption sites on the surface of the particles, but also can adsorb more substances, and due to the unique hydrophilicity of the hydrophilic colloid itself, the water absorption effect of Comparative Example 1 is more significant. After enzymolysis, the adsorption effect of the particles is significantly higher than that of Comparative Example 1 and ordinary corn starch without enzymolysis, indicating that Comparative Example 2 and Example 1 both have better pore structure, which is consistent with the SEM results in the previous text. However, under the observation of microscope and scanning electron microscope, the particle structure of Comparative Example 2 collapses, so the adsorbed substances are easy to fall off. The adsorption effect of Example 1 is significantly better than that of Comparative Example 2, and the adsorption rate of water, oil, vitamin C or methylene blue shows the same trend. This may be because the two-step method of "melt coating" and "directional hydrolysis" not only forms holes in the particles, but also has little damage to the particle structure. The particles still have a relatively complete structure, which is more conducive to the adsorption and sustained release of porous starch on bioactive factors. Compared with native starch, the adsorption rates of porous starch prepared by the two-step method of "melt coating" and "directional hydrolysis" on water molecules, oil molecules, vitamin C and methylene blue increased by 103.24%, 138.33%, 55.90% and 73.70% respectively. This data fully demonstrates that the two-step method of "melt coating" and "directional hydrolysis" has significant advantages in improving the adsorption effect of starch particles.
[0079] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention are equivalent and should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a structurally stable porous starch, characterized in that: The following steps are involved: (1) Melt coating: Add a hydrophilic colloid into deionized water to prepare a solution, then add starch, mix well, and obtain a composite suspension, heat it to the temperature at which the crystal begins to melt, and then vacuum freeze-dry and sieve to obtain melt-coated starch; (2) Directed hydrolysis: Add the molten coated starch to a citric acid-disodium hydrogen phosphate buffer solution and mix well to obtain a starch-buffer solution suspension. Add enzyme to carry out an oscillating hydrolysis reaction. After the reaction is completed, adjust the reaction solution to alkaline to terminate the reaction, then adjust to neutral, and finally centrifuge, wash, vacuum freeze-dry, grind and sieve to obtain a structurally stable porous starch.
2. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (1), the hydrophilic colloid is one or a mixture of two or more of pectin, locust bean gum, carrageenan, gum arabic, gelatin, chitosan, dextran, xanthan gum, cellulose or hemicellulose in any proportion.
3. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (1), the starch is one or a mixture of two or more of ordinary corn starch, waxy corn starch, rice starch, millet starch, wheat starch, potato starch, tapioca starch, sweet potato starch, mung bean starch, pea starch, water chestnut starch or lotus root starch in any proportion.
4. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (1), the amount of the hydrophilic colloid added is 0.1% to 10% of the dry basis weight of the starch.
5. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (1), the temperature of the heating treatment is a temperature at which the starch crystals are completely melted as measured by a differential scanner and fluctuates within ±5°C, and the heating treatment time is 15 min to 100 min.
6. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (2), the amount of molten coated starch added to every 100 mL of citric acid-disodium hydrogen phosphate buffer solution is (25-45) g, and the pH value of the citric acid-disodium hydrogen phosphate buffer solution is 5.6-6.
4.
7. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (2), the enzyme is one or a mixture of any proportion of α-amylase, β-amylase, γ-amylase, isoamylase or saccharifying enzyme, and the amount of the enzyme added is 40U / g to 180U / g of the dry basis mass of starch.
8. The method for preparing the structurally stable porous starch according to claim 1, characterized in that: In step (2), the conditions of the oscillation hydrolysis reaction are 120-200 r / min, 25° C.-60° C., and 4 h-12 h.
9. The method for preparing the structurally stable porous starch according to any one of claims 1 to 8, characterized in that: In step (2), the centrifugal speed is 3000-4000 r / min, the time is 5 min-25 min, and the screening is through a 200-mesh sieve.
Citation Information
Patent Citations
Method for improving properties of starch-base edible packaging film by adding hydrophilic colloid
CN104059248A
Technology for modifying modified starch
CN105399843A
Preparation method of corn porous starch
CN108018322A
Preparation process and application of lipophilic composite modified starch
CN117551712A
Cited By
Preparation method of high-strength high-absorptive porous starch
CN122855583A